Exploring the Perceptions of High School Students on the Use of Quizizz as a Scanning Reading Tool for Assessment - Ali, Muhammad Hilmi Muzaffar; Asari, Slamet (Jetlal, 2024)
One of the abilities that should come first is reading comprehension as it allows students to learn more on their own. Supported by developments over time, the existence of the internet and mobile devices has made humans more advanced in many things, one of which is reading. As mobile devices are today used as a natural means of communication and entertainment, they replace the traditional acquisition of knowledge and memorization of information. There are many recent discoveries in mobile technology such as applications and websites, quizizz is one of them. Quizizz is a quiz distribution application that is easy to use and understand by students. The research focus on measuring students' perceptions of Quizizz as an assessment tool, examining the extent to which Quizizz usage affects student perception in learning, and investigating its correlation with students' reading comprehension. This study uses a mix method. The participant consists of 35 students from 12 MIPA 3 with 15 male and 20 female. The data were collected through questionnaires and scanning reading question. The result of this study reveals that most students have positive perceptions regarding the usage of Quizizz as a teaching media and it is suggested to English teachers for using scanning technique in teaching reading, and also using Quizizz can improve reading comprehend skill of students better.